2008
DOI: 10.1097/hjh.0b013e32830c45c3
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of metabolic syndrome in uncontrolled hypertension across Europe: the Global Cardiometabolic Risk Profile in Patients with hypertension disease survey

Abstract: Objectives The Global Cardiometabolic Risk Profile in Patients with hypertension disease survey investigated the cardiometabolic risk profile in adult outpatients with hypertension in Europe according to the control of blood pressure (BP) as defined in the European Society of Hypertension and of the European Society of Cardiology (ESH/ESC) guidelines.Methods Data on BP control and cardiometabolic risk factors were collected for 3370 patients with hypertension in 12 European countries. Prevalence was analyzed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 33 publications
8
63
0
6
Order By: Relevance
“…The overall BPcontrol rate was generally low, and significantly lower in women (30.6%) as compared with men (33.6%), driven by the observed disparity in SBP. When looking at patients with concomitant diabetes mellitus, overall BP-control rate was not only expectedly lower, but gender disparity in SBP levels was more pronounced (3.5 mm Hg); data that have been described earlier by Kjeldsen et al 12 in a large survey conducted in Europe. Although the absolute difference in BP-control rate seems somewhat small, the detected difference in mean SBP of 2.1 mm Hg (3.5 mm Hg in the diabetic population) appears to be clinically meaningful, because it has been shown that a decrease in mean SBP of 2 mm Hg is associated with a 7% reduction in ischaemic heart disease-mortality and a 10% reduction in stroke-mortality.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The overall BPcontrol rate was generally low, and significantly lower in women (30.6%) as compared with men (33.6%), driven by the observed disparity in SBP. When looking at patients with concomitant diabetes mellitus, overall BP-control rate was not only expectedly lower, but gender disparity in SBP levels was more pronounced (3.5 mm Hg); data that have been described earlier by Kjeldsen et al 12 in a large survey conducted in Europe. Although the absolute difference in BP-control rate seems somewhat small, the detected difference in mean SBP of 2.1 mm Hg (3.5 mm Hg in the diabetic population) appears to be clinically meaningful, because it has been shown that a decrease in mean SBP of 2 mm Hg is associated with a 7% reduction in ischaemic heart disease-mortality and a 10% reduction in stroke-mortality.…”
Section: Discussionmentioning
confidence: 58%
“…[8][9][10][11] As cardiovascular disease is considered to be the single largest cause of mortality in women with 70% of cardiovascular deaths attributable to modifiable risk factors, such as hypertension, it is important to better understand gender disparities in hypertension management on a worldwide basis to ensure equal standards in treatment for both, men and women. 12 This analysis from a large international survey in hypertensive patients aims at analysing, whether there are gender disparities with regard to BP levels, BP control and antihypertensive drugs usage.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing these features with the selection criteria required by the major trials, only a minority of these patients could have been enrolled. epidemiological studies also indicate that the association of arterial hypertension with other Cv risk factors or metabolic syndrome makes effective control of Bp much more difficult even if aggressive therapy is used, [70][71][72] paralleling the less effective reduction of LvH, as shown in the Losartan intervention for endpoint reduction in Hypertension (LiFe) study. 73 in the American indian cohort of the strong Heart study, left ventricular mass index tended to increase in treated hypertensive participants, over 4 years of follow-up.…”
Section: The Real Worldmentioning
confidence: 99%
“…Moreover, most ARBs have never been compared against placebo in randomized, double-blind trials and it is unknown whether ARBs as a class are capable of reducing the risk for new onset diabetes. As hypertension itself is associated with increased risk for diabetes and is often accompanied by multiple metabolic disturbances that strongly promote diabetes, [12][13][14] it is important to reduce the risk for diabetes linked to hypertension rather than to simply avoid the risk for diabetes caused by certain kinds of antihypertensive drugs. Furthermore, regardless of the ongoing controversy over whether the diabetes that develops during hypertension treatment is associated with increased cardiovascular risk, diabetes per se is a highly undesirable problem that negatively affects the quality of life in many ways and significantly increases health-care costs.…”
Section: Angiotensin Receptor Blockers: Current Limitations and Unmetmentioning
confidence: 99%